2008
DOI: 10.1080/00016340801908759
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maternal group B streptococcal colonisation in European countries

Abstract: Although there is variation in the proportion of women colonised with GBS, the range of colonisation, the serotype distribution and antimicrobial susceptibility reported from European countries appears to be similar to that identified in overseas countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
111
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 54 publications
15
111
2
9
Order By: Relevance
“…Regardless, the colonization rates observed in this study (22.5% to 26%) are consistent with those detected worldwide 2,6,8,14,16,18,20 .…”
Section: Tablesupporting
confidence: 77%
“…Regardless, the colonization rates observed in this study (22.5% to 26%) are consistent with those detected worldwide 2,6,8,14,16,18,20 .…”
Section: Tablesupporting
confidence: 77%
“…They are normal microflora in humans in the oral cavity, the intestinal tract and the vagina, where they play a beneficial role (Todar, 2012). Compared to some other authors (Barcaite et al, 2008), we found a lower prevalence of Str. agalactiae (6%), probably because the samples were taken from upper vagina not from lower part of vagina, perineum and rectum.…”
Section: Discussioncontrasting
confidence: 47%
“…U. urealyticum, M. hominis, E. coli, and Str. agalactiae commonly inhabit the lower genital tract of sexually active women (Watt et al, 2003;Waits et al, 2005;Barcaite et al, 2008). Large numbers of M. hominis are associated with BV and are an important risk factor for development of preterm labour (Lamont et al, 1987;Rosenstein et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As the culture-PCR based method, in our study, showed higher GBS detection rates, and two genetic markers were targeted, we believe that Although vancomycin is not a first line drug for prophylaxis of perinatal streptococcal disease, some enterococci and Staphylococcus aureus (28) isolates have been proving resistant to this antibiotic. This trend notwithstanding, no vancomycin-resistant GBS isolates have been identified (2,5,10,24,28). In the light of the findings, vancomycin may be considered a better option for prophylaxis of patients allergic to penicillin.…”
Section: Discussionmentioning
confidence: 99%